The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1037/0022-006x.67.5.725
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment relationships for persons with serious psychiatric disorders: The importance of attachment states of mind.

Abstract: Participants were 54 clients with serious psychiatric disorders and 21 clinical case managers. Clients' serious psychiatric disorders included Axis I diagnoses, such as schizophrenia and bipolar disorder. This study examined how attachment states of mind of both clients and case managers influenced the effectiveness of therapeutic relationships and client functioning. Client and case manager attachment states of mind interacted in predicting the working alliance and client functioning. Specifically, clients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
195
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(208 citation statements)
references
References 24 publications
9
195
1
3
Order By: Relevance
“…These results are consistent with the study of Tyrrell and colleagues (Tyrell, 1999) who found better outcomes and therapeutic alliances in patients in treatment with therapists who were more dissimilar from them on the hyperactivating/deactivating dimension of attachment. In this regard, it is important to keep in mind our other finding that this dissimilarity in personality style was based on therapists having more secure attachment styles and more positive (loving) introjects as compared to patients.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with the study of Tyrrell and colleagues (Tyrell, 1999) who found better outcomes and therapeutic alliances in patients in treatment with therapists who were more dissimilar from them on the hyperactivating/deactivating dimension of attachment. In this regard, it is important to keep in mind our other finding that this dissimilarity in personality style was based on therapists having more secure attachment styles and more positive (loving) introjects as compared to patients.…”
Section: Discussionsupporting
confidence: 82%
“…Ratings of alliance between intervener and participants are usually not explored in their own right, leaving many questions about why the intervener or participant perceive the alliance as either positive or negative, and which intervener or maternal characteristics are important for establishing a good working relationship during the intervention. In a study on effective treatment relationships with psychiatric clients, Tyrrell, Dozier, Teague, and Fallot (1999) found that concordance in attachment representations of client and case manager predicted working alliance and client functioning. Attunement between parent and intervener in interventions appears to be of equal importance for preventive parenting intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This resistance is driven by the influence the representations have upon the interpretation of others' behaviors combined with related social behaviors that cause significant others to interact with the individual in a manner that reinforces these internal working models (Zegers, Schuengel, Van Ijzendoorn, & Janssens, 2006). These attachment representations likely not only predict the quality of the developing attachment relationship between a parent and adolescent (see De Wolff & Van Ijzendoorn, 1997), but may extend to romantic relationships in adulthood (Crowell et al, 2002) and client-therapist relationships in adolescence (Tyrell, Dozier, Teague, & Fallot, 1999;Zegers et al, 2006). Attachment style is the second attachment-related construct measured in adolescence and is arguably the one most often conceptualized when casual observers contemplate attachment considerations.…”
Section: Attachment Representation Versus Attachment Stylementioning
confidence: 99%